برصغیر میں علوم اسلامیہ کے فروغ میں خانوادہ عثمانیہ (بدایوں) کے کردار کا تحقیقی مطالعہ (1235ھ تا 1435ھ) - Mazhar Hussain Bhadroo; Muhammad Abid Nadeem (Pakistan Journal of Islamic Research)
The centers of Islamic learning in different parts of Indo-Pak have played a prominent role in the advancement of social, political and education endeavours of the Muslims living in this part of the world. Amongst the different centers of Islamic scholarship, Khānwādah `Uthmāniah Badāyūn holds an exceptional position due to its uniqueness and efficacy. The `ulemā of this family, such as Maulana Abdul Majeed Qadri (D. 1263 AH), Maulana Fazal Rasool Badayuni (D. 1289 AH), Maulana Faiz Ahmed Badāyūnī (Lost. 1274 AH), Maulana Abdul Qadir Badāyūnī (D. 1319 AH), Maulana Abdul Muqtadir Qadri (D. 1334 AH), Maulana Abdul Qadeer Qadri (D. 1379 AH), Allama Usaid-ul-Haq Qadri (D. 1435 AH) and Allama Abdul Hameed Muhammad Saalim Al-Qadri, have rendered invaluable services for advancement of Islamic teaching and their services are beyond admiration. The number of publications of this family amounts to hundreds. Whereas, the compilations of their descendents and `ulemā of Madrassa Qadriya Badāyūn are in addition to those. This also examine the authenticity and historic standing of Khānwādah `Uthmāniah on the advancement and publication of Islamic theology and education. The efforts made by Khānwādah `Uthmāniah Badāyūn for the promotion of Islamic knowledge in Indo-Pak are on record and will be remembered forever.